Associations between physical activity, screen time, sleep time and selected academic skills in 8/9-year-old children - Agata Korcz; Jana Krzysztoszek; Michał Bronikowski; Marlena Łopatka; Łukasz Bojkowski (BMC, 2023)
Abstract Background High levels of physical activity (PA), low levels of screen time, combined with sufficient sleep time, provide better health benefits. However, few studies have examined the association of these behaviours with academic skills. Therefore, this study aims to determine how PA, screen time, and sleep time are related to selected academic skills of 8/9-year-old children while examining compliance with the guidelines on PA, sedentary behaviour, and sleep among this population group. Methods This cross-sectional study included 114 primary school children (50% girls) aged 8-9years old from 2nd grade. The levels of PA, screen time, and sleep were assessed using self-reported questionnaires. The selected academic skills (based on reading and writing) were assessed by a battery of methods designed to diagnose the causes of school failure in students aged 7-9. Non-linear regression was applied to build multivariate models aimed at finding the most significant predictors for the selected academic skills separately. Results Sixty-seven percent of children met the sleep guidelines, 22% met the screen time guidelines, and only 8% met PA guidelines. In terms of screen time, boys spent more time playing games than girls (p = .008). Moderate to vigorous intensity physical activity (MVPA) was associated with higher/better scores of the visual-auditory integration (B = -0.07, p = .040). Not meeting the sleep guidelines was associated with lower scores in visual-auditory integration among children (B = 0.12, p = .042). Children who did not meet the screen time guidelines had lower scores in perceptual-motor integration (B = -0.09, p = .040). Conclusions Participating in PA, limiting screen time and sufficient sleep time may benefit/support academic skills in children.